Skin Temperatures in Females Wearing a 2 mm Wetsuit during Surfing - Mackenzie E. Warner; Jeff A. Nessler; Sean C. Newcomer (MDPI AG, 2019)
The aim of this investigation was to examine regional skin temperatures in recreational female surfers’ wearing a 2 mm thick neoprene wetsuit while surfing and to compare these results to previously published data collected in males participating in an identical study. Female surfers (n = 27) engaged in surfing for at least 40 min while wearing a commercially available 2 mm full wetsuit. Skin temperature of eight different anatomical locations were measured with wireless iButton thermal sensors. Regional skin temperatures significantly differed (p < 0.001) across almost all anatomical regions. Furthermore, regional skin temperatures significantly decreased across time at all skin regions throughout an average surfing session (p < 0.001). The greatest reduction in skin temperature was observed in the lower leg (−5.4 °C). Females in the current study exhibited a significantly greater skin temperature decrease in the lower back (−15.2% vs. −10.8%, p = 0.022) and lower arm (−13.6% vs. −10.8%, p < 0.001) when compared to previous data published in males. Overall, results of the current study are consistent with data previously published on male recreational surfers. However, the current study provides preliminary evidence that the magnitude of change in skin temperature may differ between male and female recreational surfers at some anatomical locations.